Intertemporal capital budgeting - Roper, Andrew H.; Ruckes, Martin E. (Journal of Banking & Finance, 2012)
This paper analyzes the optimal capital budgeting mechanism when divisional managers are privately informed about the arrival of future investment projects. Consistent with field study evidence, an optimal allocation mechanism can include a stipulation that a capital request for discretionary investment will be declined with positive probability in the period after a significant investment was made even though this is ex post suboptimal. The model derives a number of empirical predictions regarding capital budgeting and the investment of financially constrained firms.